(untitled) (Bangladesh Journal of Animal Science, 2023)
The sense of taste has a key role in nutrient sensing and food intake in poultry. A standardized and simple method for the determination of tastant-detection thresholds is required for chemosensory research in poultry as well poultry feed formulation. The goal of the study was to evaluate the effect of aging on the behavioural taste sensitivities of broiler chickens in order to improve the efficiency of feeding through correct feed selection and ration preparation. It especially aimed to establish the threshold concentrations of five different taste components (sweet, sour, bitter, salt, and umami). Total of 15 feeding trials for broiler chicks of various ages were performed. For each taste quality, the powdered flavor active ingredients for sweet, sour, bitter, salty, and umami were selected. The actual drinking volume of water and taste solution was identified. Because the p values were less than 0.05, the concentrations of sucrose (100 mM), citric acid (50 mM), sodium chloride (20 mM), caffeine (10 mM), and mono-sodium glutamate (MSG) (100 mM) were significant. Taken together, it may be concluded that the taste active chemical sensitivity was very "concentration-dependent" manner for the aforementioned concentrations and that younger chickens have a greater sense of taste than older birds. Bangladesh Journal of Animal Science 52 (1): 22-28, March 2023